Respuesta :

Answer:

Step-by-step explanation:

Let find inverse of f(x):

f(x) = [tex]\frac{1}{x}[/tex] + 2

y = [tex]\frac{1}{x}[/tex] + 2

[tex]\frac{1}{x}[/tex] = y - 2

x = [tex]\frac{1}{y -2}[/tex]

y = [tex]\frac{1}{x -2}[/tex] is the inverse of f(x) = [tex]\frac{1}{x}[/tex] + 2

Therefore, f(x) and h(x) are not inverses.

==============

h(x) = [tex]\frac{4}{x-3}[/tex]

y = [tex]\frac{4}{x-3}[/tex]

x = [tex]\frac{4}{y-3}[/tex]

y - 3 = [tex]\frac{4}{x}[/tex]

y = [tex]\frac{4}{x}[/tex] + 3 is the inverse function of h(x)